KARAKTERISTIK MANAJER PROYEK TERHADAP KINERJA KONSTRUKSI GEDUNG DI KABUPATEN BADUNG - Widyarsana, I Putu; Martha Jaya, N.; Astawa Diputra, Gd. (JURNAL SPEKTRAN; Vol 4 No 2 (2016): Vol. 4, No. 2, Juli 2016, 2016)
Abstract Badung regency in Bali, where the tourism industry is growing very rapidly. Building continues to grow, such as hotels, villas, resorts, hospitals, and so forth. Implementation of building construction projects in Badung not be separated from the issue of costs, quality of execution and completion time of the project. These problems arise due to lack of skills / competencies project manager of the responsibility to integrate and coordinate all available resources for the achievement of project objectives. In this case the role of Project Manager will determine the success of a project. So, there should be a study of the basic capabilities that must be owned by the Project Manager, among others: Conceptual Skills, Technical Skill, and Soft Skills. Data collection is done by the method of observation and surveys. Factor analysis was conducted to identify factors / characteristics Project Manager that affect the quality of the construction project implementation performance. Multiple linear regression analysis determined the relationship of the performance characteristics of the project manager building construction projects in Badung. Factor analysis resulted in the identification of 22 variables that affect the quality of the building construction project implementation performance. Multiple linear regression analysis determines the characteristics of the Project Manager greatest influence on the quality of the building construction project implementation performance is Social Skills aspect of 33.08% compared to the other two aspects, namely the conceptual skills (32.10%) and Technical (9.40%) . The total value of the influence of the three aspects of the characteristics of the project manager of 74.58% means that there are still approximately 25.42% influenced by other factors, such as the state of nature, the environmental situation, location, and so on, the implementation of building construction projects in Badung.
Keywords: project manager, the performance of the building construction, factor analysis, regression analysis